Identifying clusters of health risk behaviors and their predictors in adult survivors of childhood cancer: A report from the French Childhood Cancer Survivor Study. Issue 10 (5th August 2020) - Pinto, Sandrine; Fresneau, Brice; Hounsossou, Hubert C.; Mayet, Aurélie; Marchi, Joeffrey; Pein, François; Journy, Neige; Mansouri, Imene; Drubay, Damien; Letort, Véronique; Lemler, Sarah; Demoor‐Goldschmidt, Charlotte; et al.
Abstract: Objective: Health risk behaviors (HRB) of childhood cancer survivors (CCS) are generally studied separately, despite the evidence suggesting that HRB are not independent. To our knowledge, few studies have examined HRB profiles in the former pediatric cancer patients. In this study, we identified HRB profiles and examined predictors engaging in unhealthy behaviors in CCS. Methods: We used data from a French cohort of CCS that includes five‐year survivors diagnosed between 1945 and 2000 and treated before reaching age 18, in five centers in France. A total of 2961 adult CCS answered a self‐reported questionnaire pertaining to HRB. Latent class analysis was used to identify HRB profiles combining physical activity, smoking, cannabis use, and alcohol drinking. Multinomial logistic analyses examined predictors for engaging in unhealthy behaviors. Results: Three HRB patterns emerged: "Low‐risk" (n = 1846, 62.3%) included CCS who exhibited the highest frequency for usual physical activity and the lowest probabilities for current smoking or cannabis use, but most drank at least moderately; "Moderate‐risk behaviors" (n = 291, 9.8%), and "High‐risk behaviors" (n = 824, 27.8%) for CCS who exhibited the highest frequencies for current smoking, cannabis use, and heavy drinking. The multivariable regression revealed that male CCS, less educated or not married were significantly more likely to be in the high‐risk behaviors group than the low‐risk group. Conclusions: As CCS remain a vulnerable population, screening for HRB should be routinized in long‐term follow‐up care and interventions targeting multiple HRB simultaneously among survivors should be developed.